Tracing the Development of Argumentive Writing in a Discourse-Rich Context. (January 2016) - Kuhn, Deanna; Hemberger, Laura; Khait, Valerie
In most assessments of students' argumentive writing and in most research on the topic, students write on topics for which they have no specific prior preparation. We examined development in the argumentive writing urban middle school students did as part of a two-year dialogic-based intervention in which students engaged deeply with a series of topics and participated in various kinds of electronic and verbal dialogic activities related to the topic. Students' achievements exceeded those typical of the extemporaneous expository writing of middle school students. The gradual developments observed over time included ones in (a) addressing and seeking to weaken the opposing position, (b) identifying weaknesses in a favored position and strengths in an opposing one, (c) connecting and integrating opposing arguments, and (d) using evidence to weaken as well as support claims. In addition to identifying a trajectory of what develops in the development of argumentive writing, these analyses support the claim of dialogic argumentation as a productive bridge to individual argumentive writing and highlight the contribution of deep engagement with the topic in enhancing writing.